2008
DOI: 10.1177/1534765608322129
|View full text |Cite
|
Sign up to set email alerts
|

Complicated grief and its relationship to mental health and well-being among Bosnian refugees after resettlement in the United States: Implications for practice, policy, and research.

Abstract: This study investigates mental health and well-being variables in a randomly selected sample of Bosnian refugees. The sample was predominately female (56%), with a mean age of 42, and 56.5% were educated at 12 years of school or less with 43.5% reporting more than 12 years of education. Four standardized research instruments that measured trauma exposure, posttraumatic stress disorder (PTSD) symptomatology, complicated grief, anxiety, depression, well-being, and general mental health (a combined measure of wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 42 publications
3
60
0
Order By: Relevance
“…This rate is generally consistent with prevalence rates found in research with Western populations (Barry, Kasl, & Prigerson, 2002;Zhang, El-Jawahri, & Prigerson, 2006). In contrast, this rate was substantially lower than those recorded in previous studies undertaken with other refugee groups and persons who had experienced traumatic loss, including individuals who had lost a loved one during the September 11 terrorist attacks (43%; Neria et al, 2007), Bosnian refugees (54%; Craig et al, 2008), and survivors of the war in Kosovo (38.3%; Morina et al, 2010). One possibility is that the discrepancy in prevalence rates is related to variations between studies regarding caseness criteria, with studies requiring functional impairment for Note.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This rate is generally consistent with prevalence rates found in research with Western populations (Barry, Kasl, & Prigerson, 2002;Zhang, El-Jawahri, & Prigerson, 2006). In contrast, this rate was substantially lower than those recorded in previous studies undertaken with other refugee groups and persons who had experienced traumatic loss, including individuals who had lost a loved one during the September 11 terrorist attacks (43%; Neria et al, 2007), Bosnian refugees (54%; Craig et al, 2008), and survivors of the war in Kosovo (38.3%; Morina et al, 2010). One possibility is that the discrepancy in prevalence rates is related to variations between studies regarding caseness criteria, with studies requiring functional impairment for Note.…”
Section: Discussionsupporting
confidence: 74%
“…Rates of PGD have varied widely across these studies, ranging from 8% among Rwandan war widows and orphans (Schaal et al, 2009) to 54% in resettled Bosnian refugees (Craig et al, 2008). In contrast, few studies have examined individual symptoms of PGD in these settings.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…First, refugees are more likely to suffer from ongoing stressors that – combined with their complex psychiatric symptoms – can have a detrimental effect on their daily functioning and that can challenge treatment outcome (Craig, Sossou, Schnak, & Essex, 2008; Nickerson et al, 2014; Steel et al, 2011). Legal procedures, being separated from family and socioeconomic disadvantages, may all contribute to increased symptom severity and block symptom reduction (Schock, Böttche, Rosner, Wenk-Ansohn, & Knaevelsrud, 2016; Schock, Rosner, & Knaevelsrud, 2015; Steel et al, 2009, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Their grief reaction is similar to complicated bereavement and ambivalent loss which are typically distinguished from depression by preoccupation, longing and searching for the deceased or missing person (Shear 2009). Both complicated bereavement and ambivalent loss have been documented in refugee communities (Craig et al 2008). Counsellor-advocates reported that for some children and young people the intensity of the grief reaction did reduce over time as they settled into life in Australia.…”
Section: Psychological Signs and Symptoms And Emotional Distressmentioning
confidence: 99%